Macrosomía: Predictive factors and complications during vaginal delivery in the National Hospital PNP Luis N. Sáenz during the years 2005 y 2006 - Joseph Paredes Torres (2019)
Objectives: To determine the predicting factors of the macrosomia and a predicting model will be elaborated. Also, to describe the complications those have, the new born and the mother during the vaginaldelivery.Methodology: For the data summary in the present study, clinical histories were used and the necessary information was registered, then the results were analyzed using the statistical program SPSS. Results: The only factors that predicted the macrosomia of isolated form were the uterine heightgreater to 34 cm. (44%) and masculine fetal sex (5%), these, like other predicting factors acquire greater orsmaller force according to the relation that settles down, reason why was elaborated fluxogram in whichthe probability for fetal macrosomia was observed.Between the complications we found the following thing: 21,1% of the cases of macrosomia presentedprolonged delivery; the 2,9% of macrosomics presented fracture of clavicle; the 31,7% of mothers withmacrosomics children presented tear at the time of the delivery, corresponding to this group the 71,4% oftears of II degree and the 100% of those of III degree; the premature membrane rupture was observed inthe 17,3% of macrosomics, and the 5,1% of the nonmacrosomics ones.Conclusions: Is necessary the identification and valuation of the predicting factors of macrosomia,taking into account the force that they acquire when being related and decide the best one via of delivery,avoiding complications during itself